2018
DOI: 10.18632/oncotarget.25385
|View full text |Cite
|
Sign up to set email alerts
|

Diminished gallbladder filling, increased fecal bile acids, and promotion of colon epithelial cell proliferation and neoplasia in fibroblast growth factor 15-deficient mice

Abstract: Fibroblast growth factor-19 (human FGF19; murine FGF15) suppresses bile acid synthesis. In FGF19 deficiency, diarrhea resulting from bile acid spillage into the colon mimics irritable bowel syndrome. To seek other consequences of FGF19/15 deficiency, we used Fgf15-/- and wild-type (WT) mice to assess gallbladder filling, the bile acid pool, fecal bile acid levels, and colon neoplasia. We fasted mice for six hours before assessing gallbladder size by magnetic resonance imaging (MRI). We measured bile acid level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Furthermore, the ability of bile acids to induce neoplasia has also been demonstrated; mice fed a diet with addition of deoxycholic acid developed more aberrant crypt foci, a precursor malignant lesion [40] as well as frank tumors [41]. Moreover, intestine-selective carcinogen treatment of mice with impaired bile acid transport and increased spillage of endogenous bile acids into the colon resulted in augmented colon neoplasia compared to wild-type mice with normal fecal bile acid levels [42,43].…”
Section: The Muscarinic Receptor In Crcmentioning
confidence: 99%
“…Furthermore, the ability of bile acids to induce neoplasia has also been demonstrated; mice fed a diet with addition of deoxycholic acid developed more aberrant crypt foci, a precursor malignant lesion [40] as well as frank tumors [41]. Moreover, intestine-selective carcinogen treatment of mice with impaired bile acid transport and increased spillage of endogenous bile acids into the colon resulted in augmented colon neoplasia compared to wild-type mice with normal fecal bile acid levels [42,43].…”
Section: The Muscarinic Receptor In Crcmentioning
confidence: 99%
“…We, and others, have shown that, like humans with FGF19 deficiency, FGF15-deficient mice have increased fecal bile acid excretion. 1215 We detected low quantities of intact CA-lys-TFA and CA-sar-TFMA in the stool, with more in stool from FGF15-deficient mice than from wild-type mice (Supporting Information: Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…These methods are likely insufficient to study dynamic, posttranslational changes in ASBT activity, necessitating the development of real-time methods. Several recent approaches have been developed to quantify the aspects of bile acid physiology in -real time (76,115,263,311,389,392,(397)(398)(399). Additionally, a recent bioluminescence-based approach relying on a CA-luciferin-conjugated probe has shown promising results for measuring real-time ASBT activity in vitro and in isolated intestinal epithelial cells (377).…”
Section: Posttranscriptional Regulation Of Asbtmentioning
confidence: 99%